INCREASING THE MECHANICAL PROPERTIES OF BIODEGRADABLE PLASTIC BASED ON POLY LACTIC ACID (PLA) WITH THE ADDITION OF COCONUT COIL (COIR) AND CHITOSAN - Dewi Silvia; R Ridwan (Politeknik Negeri Lhokseumawe, 2023)
Petroleum-based plastics that are difficult to decompose have been used for years to become the biggest environmental polluter.The solution is to replace conventional plastics such as bioplastics with the same quality as conventional plastics so that they can replace the existence of petroleum-based plastics.The innovation of combining natural polymers (poly lactic acid) with coir-chitosan fillers is able to make polymers have good mechanical properties. This study aims to see the effect of mixing the natural polymer poly lactic acid (PLA) with coir (coconut coir) and chitosan fillers. With variations in fiber mass fraction3.8 grams; 3.9 grams; 4 grams; 4.1 grams; 4.2 grand mass variation of chitosan 0.36 gr; 0.38 gr; 0.4 gr; 0.42 gr; 0.44 gr. The addition of coir and chitosan fillers affects the mechanical properties and thermal properties of the material.The synthesized composites were tested for their mechanical strength to determine material characteristics and morphological observations. In the tensile test, the highest tensile strength value was produced by a material with a mass fraction of coir 19% (w/w) and 1.8% (w/w) chitosan, which was 44.23 MPa and the lowest tensile strength value was produced by a material with a mass fraction coir 21% (w/w) and chitosan 2.2% (w/w) of 31.48 MPa. Based on test results Differential Thermal Analysis sample with coir modification 20% (w/w) chitosan 2% (w/w) has the best thermal stability among other samples where the sample begins to degrade (on set) at 461.77 (oC) and stops experiencing degradation (end set ) at a temperature of 531.48 (oC). The results of the morphological test using the SEM tool show that the surface structure of the PLA79.2% sample is more homogeneous due to coir (coconut coir) and chitosan chains are well dispersed into the poly lacti acid (PLA) interlayer.Â Keywords : Bioplastics, Coir, Chitosan, Biodegradation, Natural Polymers.Â